Kindness as Ethics-in-Practice in the business curriculum (Journal of Applied Learning and Teaching, 2022)
This research explores the pedagogic potential of kindness as a taught construct within a business ethics programme. Kindness in the curriculum is a topic often taught in early years’ education (Kindness Curriculum, 2020) but seldom at tertiary level and this research will investigate the intrinsic and extrinsic reasons for this context (Caldwell & Bird, 2015). Business studies can provide students with the knowledge and skills essential to leading and managing people and resources. Inter alia, business ethics teaches the fundamentals of refraining from corruption and unfair competition. Furthermore, business ethics programmes might eschew traditional ethical theory, promoting instead such constructs as Triple Bottom Line (TBL) thinking (Giddings, 2002), Corporate Social Responsibility (CSR) and Corporate Citizenship. This research considers the taught benefits of modelling philanthropy (kindness delivered at the corporate level) as one positive aspect of business ethicality.Instilling dispositions towards ethical behaviour (‘virtues’) at both the individual and company level remains a key goal of business ethics education. The ‘humane’ virtues as conceptualised within the modern Positive Psychology movement (Banicki, 2014; Peterson & Seligman, 2004) provide a theoretical underpinning for understanding kindness as a behavioural disposition, a tendency to ‘tend and befriend’ (Peterson & Seligman, 2004) that reliably generates ethical businesses grounded in ethical employees (Sternberg, 2001). This research argues that, for a business ethics course, business viewed through the lens of kindness should not be seen through the eyes of the student or the practitioner as an extracurricular activity but deconstructed as ethics-in-practice. The practice-based research intervention is in the form of a one-day student enrichment activity. The enrichment activity takes the form of a case study which looks at kindness through the lens of philanthropy. Students analyse a new case study exploring business philanthropy intervention, then complete a survey to review their opinion on key aspects of ethicality in business. Students evaluated the interconnectedness between ethics and how positive psychology is embedded in business. Thematic analysis was used to determine (a) ways of measuring values in action by doing good, and (b) changes in students’ understanding of the role of ethics in business upon completion of the intervention. However, in summary our research suggests that kindness embedded in the business curriculum and academics have a key role in facilitating this improvement.